Descriptive analysis of the cost of implanting forage cactus in rainfed planting in the semiarid region of Alagoas: a case study-Análise descritiva do custo de implantação de palma forrageira em plantio de sequeiro no Semiárido alagoano: um estudo de caso - Deneson Oliveira Lima; Cleyton de Almeida Araújo; Lenivaldo Manoel de Melo (Universidade Estadual de Alagoas, 2020)
In the Northeastern Semi-arid, family farming presents a relationship between land, labor and family. The production processes were structured historically empirically without an effective presence of technical assistance for agricultural production. Alagoas represents 72% of the workforce employed in rural areas, traditionally with the culture of not using bookkeeping as a management tool. Its lack is an obstacle and it camouflages the real costs of implantation of the agricultural systems, including those of implantation of palms. Aiming at these factors, a descriptive analysis of the cost of implantation of forage palm (Napolea cochenillifera) in a densified system in a family property was carried out. Costs were measured with: Manure application, plowing, coveamento, seeds, distribution, coverage and two clean and measurement of the cost of labor. The results point to the acquisition of the seeds, which compose the costs of higher burden to the detriment of the others. The analyzed reality presents no distant variation for other spatialities reported in the bibliography. The realization of productive costs and then a comparison with the literature enables the producer to know the real value of his work, helping to make decisions